Anillin regulates cell-cell junction integrity by organizing junctional accumulation of Rho-GTP and actomyosin - Reyes, Ciara C. (2014)
Anillin is a scaffolding protein that organizes and stabilizes actomyosin contractile rings and was previously thought to function primarily in cytokinesis [1–10]. Using Xenopus laevis embryos as a model system to examine Anillin’s role in the intact vertebrate epithelium, we find that a population of Anillin surprisingly localizes to epithelial cell-cell junctions throughout the cell cycle, whereas it was previously thought to be nuclear during interphase [5, 11]. Further, we show that Anillin plays a critical role in regulating cell-cell junction integrity. Both tight junctions and adherens junctions are disrupted when Anillin is knocked down, leading to altered cell shape and increased intercellular spaces. Anillin interacts with Rho, F-actin, and Myosin II [3, 8, 9], all of which regulate cell-cell junction structure and function. When Anillin is knocked down, active Rho (Rho-GTP), F-actin, and Myosin II are misregulated at junctions. Indeed, increased dynamic “flares” of Rho-GTP are observed at cell-cell junctions, while overall junctional F-actin and Myosin II accumulation is reduced when Anillin is depleted. We propose that Anillin is required for proper Rho-GTP distribution at cell-cell junctions and for maintenance of a robust apical actomyosin belt, which is required for cell-cell junction integrity. These results reveal a novel role for Anillin in regulating epithelial cell-cell junctions.